Model empowerment of nutmeg farmers through the diffusion process of innovation diversification of nutmeg commodity (Myristica fragrans Houtt) in Ternate City (Case study in Ngade and Marikurubu Villages) - Anggraini, Putri Ayu; Sugiyanto, Sugiyanto; Cahyono, Edi Dwi (Agrikan: Jurnal Agribisnis Perikanan, 2022)
This study purpose to find an effective empowerment model in the innovation diffusion activity of nutmeg commodity diversification in Ternate City. The sample used was 30 respondents. The data obtained for this study consisted of two sources, namely primary and secondary data. The analysis used in this research is Structural Equation Modeling (SEM) analysis. Based on the results of the study showed that the model of farmer empowerment through the diffusion of effective diversification innovations in Marikurubu Village and Ngade Village, Ternate City, North Maluku Province requires several variables including Human Resources Variables consisting of Extension Officers and Farmers. greatly affect other variables. Then followed by process variables including Material and Media, where the material most desired by respondents was Processed Balm using the help of infocus media. The output that will be produced is a change in the knowledge, attitudes and skills of respondents in implementing materials about processed nutmeg products to be empowered and able to compete in the market.